Structural change in agriculture under capacity constraints: An equilibrium approach - Stefan Kersting; Silke Hüttel; Martin Odening (Universität Rostock, Institut für Volkswirtschaftslehre, 2015)
This paper analyses the impact of a tradable production quota on firm entry and exit in the agricultural industry. We develop a dynamic stochastic equilibrium framework considering that a release of production capacity by exiting firms affects the investment options for entrants. Firms' investment and exit decisions depend on future output and quota prices, which in turn will be affected by the evolution of industry structures themselves. Contrary to many static models we find that introducing a quota system may foster structural change. A tradable quota increases the liquidation value and makes inefficient firms cease production despite higher output prices.
Keywords: D41; L11; Q11; 330; dynamic stochastic equilibrium; production quota; firm entry and exit; dairy sector